2021
DOI: 10.1097/cpt.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Ultrasound Assessment of Exercise-Induced Endothelial Shear Stress of the Brachial and Carotid Arteries

Abstract: Endothelial shear stress (ESS) has a possible effect on regulation of gene expression in the protection against atherosclerosis. During exercise, ESS should increase as systolic blood pressure and heart rate (HR) increase too; however, it is hard to determine ESS changes during exercise. Imaging ultrasound assessment of the brachial and the carotid arterial blood flow during exercise might help to estimate exercise-induced ESS. We present here the methodology at the Clinical Applied Physiology Laboratory to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Unfortunately, the authors were not able to determine ESS as they found some technical difficulties with ultrasound imaging during their protocol. These technical difficulties were avoided in the current study by using a customized, patent-pending cervical probe holder placed on the participant’s neck ( Gurovich et al, 2021a ; Morales-Acuna et al, 2020 ). Nevertheless, Jiang et al found a significant increase in carotid artery blood flow velocity, up to 52% from baseline values, during exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, the authors were not able to determine ESS as they found some technical difficulties with ultrasound imaging during their protocol. These technical difficulties were avoided in the current study by using a customized, patent-pending cervical probe holder placed on the participant’s neck ( Gurovich et al, 2021a ; Morales-Acuna et al, 2020 ). Nevertheless, Jiang et al found a significant increase in carotid artery blood flow velocity, up to 52% from baseline values, during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Then, resting blood pressure was obtained using an automated brachial blood pressure cuff (BP760, Omnron Healthcare, Inc., Lake Forest, IL, United States). In addition, and at the beginning of every visit, hematocrit (HemataStat II Hematocrit Analyzer, Separation Technology Inc., Sanford, FL, United States) and resting blood lactate (BLa) levels (Lactate Plus, Nova Inc., Boston, MA, United States) were obtained from the lower end of the earlobe as previously described ( Rascon et al, 2020 ; Gurovich et al, 2021a ). Then, for session 1, subjects completed 3 maximal strength tests (Squat, Bench Press, and Biceps curls), then subjects rested for at least 30 min ( Tagesson and Kvist, 2007 ; Neto et al, 2015 ; García-Ramos et al, 2019 ) and performed a graded exercise test on the treadmill (Trackmaster TMX58, Newton, KS, United States) to determine maximal oxygen consumption (VO 2 max) and lactate threshold.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a lack of information about endurance exercise intensity and its relationship with molecular changes. The present study used human in vivo exercise-induced ESS 16 to unveil the relationship between exercise intensity and molecular changes in the endothelial cells and provide evidence of precision medicine to clinicians.…”
Section: Discussionmentioning
confidence: 99%